Regulation of mitotic clonal expansion and thermogenic pathway are involved in the antiadipogenic effects of cyanidin-3-O-glucoside - Molonia, Maria Sofia; Salamone, Federica Lina; Muscarà, Claudia; Costa, Gregorio; Vento, Grazia; Saija, Antonella; Speciale, Antonio; Cimino, Francesco (Frontiers in Pharmacology, 2023)
Obesity is a metabolic diseaseorder characterized bywith an increased increase both in cell size (hypertrophy) as well asand in cell number (hyperplasia) through thefollowing differentiation of new adipocytes. Adipogenesis is a well-orchestrated program involving in which mitotic clonal expansion (MCE) during occurs in the early step followed by the late terminal differentiation one. The aAim of this the study was to evaluate the in vitro effects of cyanidin-3-O-glucoside (C3G), an anthocyanin present in many fruits and vegetables, during in the early or late phase of 3T3-L1 preadipocytes differentiation. C3G exposure during in the early phase of the adipogenic adipogenesis process induced a more marked reduction of CCAAT/enhancer-binding protein-β (C/EBPβ), peroxisome proliferator-activated receptor γ (PPAR-ɣ) and fatty acid synthase (FasnASN) expression than late phase exposure and these effects were associated to a reduced MCE with cell cycle arrest at G0/G1 phase via p21 expression. Furthermore, C3G exposure during the early phase activated AMPactivated protein kinase (AMPK) pathway better than in the late phase stimulatingpromoting the developmentenhancement of beige-like adipocytes. In fact, C3G induced thermogenic biomarkers uncoupling protein-1 (UcpCP-1) and peroxisome proliferator-activated receptor-gamma coactivator-1 alpha (PgcGC-1α) and these effects were more evident during early phase exposure. Our data demonstrate that C3G reduces the terminal adipogenic process affecting the early phase of differentiation and inducing a thermogenic program.